ASSESSMENT OF INDICATIONS OF LOWER SEGMENT CESAREAN SECTION AT TERTIARY CARE CENTER: A RETROSPECTIVE STUDY - MEENA, NIDHI; PARVEEN, SABA; NAGAR, TEENA; MEENA, NARESH KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Background: Cesarean section (CS) is one of the most common and widely performed surgical procedures in obstetrics in India and Worldwide. It is mainly evolved as a lifesaving procedure for mother and fetus during the difficult delivery. To study, various indications for the lower segment CS at our tertiary care center were the objective of the present study. Methods: This is a descriptive, retrospective study of all the patients who were underwent CS in the Department of Obstetrics and Gynecology, Jhalawar Medical College, Jhalawar from January 1, 2021, to March 31, 2021 for the duration of 3 months. Data of patients who delivered by C-Section in our hospital during the defined study period were recorded and a statistical analysis was done for various indications of the lower segment CS (LSCS). Results: The total numbers of women delivered by CS over the study period were 806 among these 339 (42.05%) patients were primiparous and 467 (57.95%) were multiparous. 550 (68.23%) cases were from age group 20–25 years and 153 (18.98%) were had age group 26–30 years, 20 (2.48%) were from age group below 19 years, and 76 (10.29%) patients were above 31 years age. The previous LSCS was the leading indication to the LSCS (31.14%) followed fetal distress (13.88%), malpresentation 95 (11.78%) (including breech presentation in maximum women (86), transverse and oblique lie (9 each), and face presentation (3)) (11.78%), meconium stained liquor with fetal distress 60 (7.44%), severe oligohydramnios 48 (5.95%), non-progress of labor 32 (3.97%), cephalopelvic disproportion 23 (2.85%), pre-eclampsia 20 (2.48%), obstructed labor 19 (2.35%), big baby 19 (2.35%), pregnancy-induced hypertension 18 (2.23%), maternal request and post-dated pregnancy 15 (1.86%) each, gestational hypertension and eclampsia 11 (1.36%) each, placenta previa 10 (1.24%), induction failure 8 (0.99%), and intrauterine growth retardation and antepartum hemorrhage 7 (0.86%) and 14 (1.73%). Patients had other indications such as Abruptio placentae, gestational diabetes, twin pregnancy, uterine rupture, and deep transverse arrest. Conclusions: In this study, CS rate (40.68%) is found to be higher as compared to other studies and the WHO guidelines. CSs rate is high probably because Jhalawar Medical College, Jhalawar acts as a government tertiary care center. The previous LSCS was a common indication in 31.14% of mothers in present study. Besides, previous LSCS, fetal distress, malpresentation (Breech presentation/transverse lie, oblique lie, and face presentation) MSL with fetal distress, and severe oligohydramnios were the common indications for LSCS, which are seen in the present study.